Domestic coal mining optimization under global market conditions - Stohniy O.V.; Kaplin M.I.; Bilan T.R. (General Energy Institute of the National Academy of Sciences of Ukraine, 2013)
The article presents reviews of coal industry development models by domestic and foreign authors. Their specific features as well as possibilities of taking different aspects of coal production, supply and consumption in the overall energy balance of the country into account are pointed out. The impact of currently available market price setting mechanisms upon the industry regulation and promising ways of reorganization of the branch, as well as reconstruction and modernization of certain coal mines have been analyzed. The proposed model of the mining industry structure optimization takes proper account of competitive principles of domestic mine enterprises functioning under the world’s coal market conditions. The model allows for meeting the needs of the economy for energy and coking coal by summing up the volumes of domestically produced and imported coal with regard to the structure of the demand, transportation restrictions on imported volumes and energy security requirements of Ukraine. The prospects for applying the proposed model structure to a multi-period simulation of the coal mining facilities development with regard to effectiveness of investments into the coal sector of economy are outlined.